2018
DOI: 10.1021/acs.langmuir.8b03129
|View full text |Cite
|
Sign up to set email alerts
|

Organic Fluorophore Coated Polycrystalline Ceramic LSO:Ce Scintillators for X-ray Bioimaging

Abstract: The current effort demonstrates that lutetium oxyorthosilicate doped with 1–10% cerium (Lu2SiO5:Ce, LSO:Ce) radioluminescent particles can be coated with a single dye or multiple dyes and generate an effective energy transfer between the core and dye(s) when excited via X-rays. LSO:Ce particles were surface modified with an alkyne modified naphthalimide (6-piperidin-1-yl-2-prop-2-yn-1-yl-1H-benzo­[de]­isoquinoline-1,3-(2H)-dione, AlNap) and alkyne modified rhodamine B (N-(6-diethylamino)-9-{2-[(prop-2-yn-1-ylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…We observed no toxicity in primary neuronal cultures following 24 h of LSO:Ce microparticle exposure, consistent with another study using coated LSO:Ce nanoparticles (Burdette et al, 2019). In acute hippocampal slices, there was no reactivity of the astrocytes as assessed by GFAP staining or decrease in the maximal strength of basal transmission assessed by I/O curves at CA3-CA1 synapses.…”
Section: Discussionsupporting
confidence: 92%
“…We observed no toxicity in primary neuronal cultures following 24 h of LSO:Ce microparticle exposure, consistent with another study using coated LSO:Ce nanoparticles (Burdette et al, 2019). In acute hippocampal slices, there was no reactivity of the astrocytes as assessed by GFAP staining or decrease in the maximal strength of basal transmission assessed by I/O curves at CA3-CA1 synapses.…”
Section: Discussionsupporting
confidence: 92%
“…However, in order to demonstrate that this noninvasive delivery method produced working opsin proteins Wang et al needed to implant an optical fiber for light activation. RLPs provide an alternative to implanted optic fibers and light emitting diodes (LEDs) and have been shown to be nontoxic to neurons [27], [28]. Here, we confirm that we are able to noninvasively deliver RLPs to the rat hippocampus using FUS BBB opening (Figure 1).…”
Section: Discussionsupporting
confidence: 71%
“…In order to overcome these limitations, we are working to replace fibers with novel lightemitting core-shell nanoparticles that can be activated noninvasively with X-ray exposure and can be strategically deposited such that they provide a more uniform distribution of light [27], [28]. Though further testing is still needed, these radioluminescent particle (RLPs) do not appear to interfere with neuronal functioning [29].…”
Section: Introductionmentioning
confidence: 99%
“…LSO:Ce is a scintillator that has been extensively characterized (Melcher and Schweitzer, 1992;Roy et al, 2013) and used in multiple medical devices (Stratos et al, 2010;Roy et al, 2013;Burdette et al, 2019). Cerium forms the luminescence center in LSO, and the emission spectrum makes it well suited for optogenetics applications using ChR2 (Berndt et al, 2011;Lin, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that radioluminescent LSO:Ce microparticles are biocompatible with neuronal health and function (Bartley et al, 2019), and thus potentially useful for X-ray optogenetics. LSO:Ce has been widely studied as a scintillator, and has been shown to emit visible light in response to X-ray (Spurrier et al, 2007;Valais et al, 2008;Burdette et al, 2019). The LSO host lattice provides two potential Lu 3+ sites that Ce 3+ can substitute, with the Ce1 site surrounded by 7 oxygen neighbors while the Ce2 site has 6 oxygen neighbors.…”
Section: Lso:ce Radioluminescence Is Appropriate For Chr2mentioning
confidence: 99%